2003
DOI: 10.1097/01.phm.0000056989.67763.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum Toxin Type A on Cerebral Palsy with Upper Limb Spasticity

Abstract: Our findings support the premise that botulinum toxin type A injections are effective in reducing upper limb spasticity and in improving movement pattern and fine motor function of patients with spastic cerebral palsy. A reduction in caregivers' burden and improved quality of life were demonstrated through the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 24 publications
5
37
0
2
Order By: Relevance
“…Furthermore, spasticity is a major risk for secondary articular damage: contractures, pain and vitiated postures. Spasticity can be relieved by means of systemic and local drug treatments; in particular botulinum toxin (BT) has been much used to manage spasticity in several anatomical areas in a variety of conditions such as multiple sclerosis [10,27,44,50], cerebral palsy [17,20,28,41,58], and traumatic brain injury [49,57]. BT plays a role in the management of upper and lower limb spasticity also in hemiparetic patients after stroke [7,11,25,35,43,47,51,59].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, spasticity is a major risk for secondary articular damage: contractures, pain and vitiated postures. Spasticity can be relieved by means of systemic and local drug treatments; in particular botulinum toxin (BT) has been much used to manage spasticity in several anatomical areas in a variety of conditions such as multiple sclerosis [10,27,44,50], cerebral palsy [17,20,28,41,58], and traumatic brain injury [49,57]. BT plays a role in the management of upper and lower limb spasticity also in hemiparetic patients after stroke [7,11,25,35,43,47,51,59].…”
Section: Introductionmentioning
confidence: 99%
“…However, with regard to arm-hand function in children with cerebral palsy (CP), a recent systematic review concluded that there is very little evidence to guide the choice of treatment (Boyd et al 2001). Beside some uncontrolled studies (Wall et al 1993, Hurvitz et al 2003, Yang et al 2003, only two small randomized studies of BTX-A in the treatment of arm function problems in children with CP have been published. In a randomized, doubleblind placebo-controlled study describing the effects of BTX-A injections into the upper limb in 14 patients with CP, Corry et al (1997) found a significant increase in active elbow and thumb extension, and a significantly reduced tone at wrist and elbow, at 12-week follow-up.…”
mentioning
confidence: 99%
“…BTX-A injections have previously been identified as a safe treatment in CP with side-effects in the upper limb being few, minor, and transient, [5][6][7]21,22 and occurring more often with high doses. 10 …”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Occupational or physical therapy is usually provided with BTX-A. Occupational therapy has been found to be effective in enhancing functional outcomes in the upper limbs of children with CP who received BTX-A.…”
mentioning
confidence: 99%